1981
DOI: 10.1002/app.1981.070261134
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of borate crosslinked poly(vinyl alcohol) gels

Abstract: SynopsisBoric acid does not introduce crosslinks in poly(viny1 alcohol) solutions, but gelation does occur in the presence of cations. In this experimental study, the dynamic mechanical properties of these gels were determined using test-tube torsion pendulums and an air-bearing torsion pendulum. The modulus at a fixed concentration of polymer and boric acid increases with increasing sodium ion concentration up to the point where the atom ratio of sodium to boron reaches 1. Higher sodium concentrations do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 11 publications
(2 reference statements)
6
33
2
Order By: Relevance
“…In the Shibayama model [57], also shown in Fig.11, also sodium ions are needed in the process. This is in agreement with Cheng and Rodriguez [58] who demonstrated that the addition of boric acid without sodium anions to aqueous PVA solutions has almost no effect on the gelation properties. Measurements by Beltman [51] demonstrate first that the viscoelastic properties of those gels are strongly dependent on temperature and secondly that the PVA/borate gels are temporary networks, with terminal relaxation times varying from 0.02 to 2 s and storage plateau moduli,G e , varying from 1000 to 4500 N/m 2 in the temperature range from 75 ºC to 15 ºC.…”
Section: Poly(vinyl Alcohol) + Boratesupporting
confidence: 92%
See 1 more Smart Citation
“…In the Shibayama model [57], also shown in Fig.11, also sodium ions are needed in the process. This is in agreement with Cheng and Rodriguez [58] who demonstrated that the addition of boric acid without sodium anions to aqueous PVA solutions has almost no effect on the gelation properties. Measurements by Beltman [51] demonstrate first that the viscoelastic properties of those gels are strongly dependent on temperature and secondly that the PVA/borate gels are temporary networks, with terminal relaxation times varying from 0.02 to 2 s and storage plateau moduli,G e , varying from 1000 to 4500 N/m 2 in the temperature range from 75 ºC to 15 ºC.…”
Section: Poly(vinyl Alcohol) + Boratesupporting
confidence: 92%
“…Measurements by Beltman [51] demonstrate first that the viscoelastic properties of those gels are strongly dependent on temperature and secondly that the PVA/borate gels are temporary networks, with terminal relaxation times varying from 0.02 to 2 s and storage plateau moduli,G e , varying from 1000 to 4500 N/m 2 in the temperature range from 75 ºC to 15 ºC. From the height of the rubber plateau of results presented by Beltman [51], by Schultz and Myers [59] and by Koike et al [60], the present author [4,18] has calculated the crosslinking enthalpy ΔH o to be -11.3±0.7 kJ/mol, which is quite in agreement with Cheng and Rodrigues [58] who reported a value of 10.9 kJ/mol. Terminal relaxation times, as determined from Beltman's measurements, plotted vs. reciprocal temperature enabled the present author to calculate the heat of activation E a to be 75 kJ/mol.…”
Section: Poly(vinyl Alcohol) + Boratesupporting
confidence: 85%
“…Because these experiments were run at the same pH value, no account needed to be given to M. A straight line is observed in agreement with theory and published data. [2,3,14] FigFigure 3. Correlation between visco-elasticity and total boron concentration; 3 g HPG/L, pH 10.04 ± 0.04.…”
Section: Resultsmentioning
confidence: 97%
“…[5] Many authors have assumed borate is the reactive species [1,2,5,[8][9][10][11][12][13][14][15] while others have assumed cations to be involved. [14] In a few cases boric acid was proposed as the reactant but merely because the reactions took place at very low pH values. [13] Tetraborate was assumed to be the crosslinking reactant by Khomutov et al, which is more in line with the proposed mechanism covered in this paper because it contains trivalent boron.…”
Section: Introductionmentioning
confidence: 99%
“…The kind of linkage which forms has been largely debated and in particular two models have been proposed. The first one suggests that the linkage between diols and borate ions has a mixed physical and chemical nature [6], while the second one implies only dynamic chemical cross-links between PVA chains and borate ions [7][8][9] and considers two types of interaction: monodiol complexation and crosslinking. After reaction the polymer chain behaves as a polyelectrolyte with electrostatic repulsions, resulting in an expansion of the network [10].…”
Section: Introductionmentioning
confidence: 99%